(3GdaJM aj GdJOGhj ef LejY GdCeQGV hGdTcGhjs - (3CHh SYjO Hf EHQGgje GdeZQHj GdYdGFjs ((3eOjfg GdQedI s)
(3ChdgG (B:s
(3hdeG cGfJ GdCOhjI , hGdEZPjI eGOI dMaX (B[(3UMI(B] (3GdEfSGf , hgjhdi deOGhGI CSGbGe GdCHOGf s
(3BNQgG (B:s
(3gh GdHdM PcQ ai MQa GdHGA MQa GdZjf ZdfGf gh GdLOhGQ PcQ ai MQa GdLje hcGf GdaQGZ ef gPg GdfSNI s
(3eQJH HWQjbI GdLOGhds
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B890 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdKGfi (B- (3U (B136 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs